Maternal obesity - Gillman, Matthew W.; Poston, Lucilla (Cambridge medicine, 2012)
Afflicting more than 300 million women across the globe, obesity has profound effects on health during pregnancy and on the wellbeing of the unborn child. In the face of such a challenging pandemic, this book reviews the latest research and provides up-to-date advice on clinical management. Maternal Obesity addresses the adverse effects of obesity among women of childbearing age, including infertility, medical complications, problems in labor, and adverse birth outcomes, and it reviews evidence that the obese mother's in utero environment has long-lasting influences on the health of the developing child. Chapters cover basic, clinical, and population perspectives, providing a range of valuable information from mechanistic insight through to public health and policy implications. Invaluable for obstetricians, gynaecologists, paediatricians, general and family physicians, subspecialists in obstetric and paediatric medicine, midwives, and dietitians, as well as researchers and public health policy makers seeking to tackle the burden of maternal obesity-related illness